Resting-state functional connectivity is modulated by cognitive reserve in early Parkinson’s disease - Di Tella, Sonia; De Marco, Matteo; Baglio, Francesca; Silveri, Maria Caterina; Venneri, Annalena (Frontiers in Psychology, 2023)
Background: Fronto-striatal disconnection is thought to be at the basis of dysexecutive symptoms in patients with Parkinson's disease (PD). Multiple reserve-related processes may offer resilience against functional decline. Among these, cognitive reserve (CR) refers to the adaptability of cognitive processes.We tested the hypothesis that functional connectivity of pathways associated with executive dysfunction in PD is modulated by CR.Methods: Twenty-six PD patients and 24 controls underwent resting-state functional magnetic resonance imaging. Functional connectivity was explored with independent component analysis and seed-based approaches. The following networks were selected from the outcome of the independent component analysis: default-mode (DMN), left and right fronto-parietal (l/rFPN), salience (SalN), sensorimotor (SMN), and occipital visual (OVN). Seed regions were selected in the substantia nigra and in the dorsolateral and ventromedial prefrontal cortex for the calculation of seed-based functional connectivity maps. Educational and occupational attainments were used as CR proxies.Results: Compared with their counterparts with high CR, PD individuals with low CR had reduced posterior DMN functional connectivity in the anterior cingulate and basal ganglia, and a bilateral reduction of connectivity in fronto-parietal regions within the networks defined by the dorsolateral and ventrolateral prefrontal seeds. Hyper-connectivity was shown within medial prefrontal regions when comparing low-CR PD with low-CR HC.Conclusions: CR may exert a modulatory effect on functional connectivity involving basal ganglia and executive-attentional fronto-parietal networks. In PD patients with low CR, attentional control networks seem to be downregulated, whereas higher recruitment of medial frontal regions suggests a compensation via an upregulation mechanism. This upregulation might contribute to maintaining efficient cognitive functioning when the posterior cortical function is progressively reduced.